2020
DOI: 10.3390/nu12020378
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals and Hypertensive Disorders in Pregnancy: The Available Clinical Evidence

Abstract: The aim of the present critical review is to summarize the available clinical evidence supporting the use of some dietary supplements that have been shown to lower blood pressure in hypertensive pregnant women. A systematic search strategy was carried out to identify trials in MEDLINE (National Library of Medicine, Bethesda, Maryland, MD, USA; January 1980 to September 2019) and the Cochrane Register of Controlled Trials (The Cochrane Collaboration, Oxford, UK). The terms ‘nutraceuticals’, ‘dietary supplements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 52 publications
(59 reference statements)
0
17
0
2
Order By: Relevance
“…[ 20 ] While Silvia Fogacci's researchers found that vitamin D supplementation may be useful in preventing preeclampsia and the development of hypertensive disorders in pregnancy. [ 21 , 22 ] Insufficiency/deficiency of vitamin D during pregnancy would seriously affect the growth and development of fetal bones, thereby affecting the breast circumference, head circumference and length of the fetus, greatly increasing the birth probability of SGA. [ 23 ] The mortality and disease risk of SGA in the perinatal period were significantly higher than those of normal-weight newborns, and they would also have cognitive impairment, low learning ability, and low adult lifelong height in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] While Silvia Fogacci's researchers found that vitamin D supplementation may be useful in preventing preeclampsia and the development of hypertensive disorders in pregnancy. [ 21 , 22 ] Insufficiency/deficiency of vitamin D during pregnancy would seriously affect the growth and development of fetal bones, thereby affecting the breast circumference, head circumference and length of the fetus, greatly increasing the birth probability of SGA. [ 23 ] The mortality and disease risk of SGA in the perinatal period were significantly higher than those of normal-weight newborns, and they would also have cognitive impairment, low learning ability, and low adult lifelong height in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-eclampsia is a severe vascular complication of pregnancy. A growing collection of literature suggests that attention needs to be focused on the possible effect of CoQ 10 during pregnancy-related hypertensive disorders [160].…”
Section: Pre-eclampsiamentioning
confidence: 99%
“…It is produced by plants under the action of exogenous stimuli, such as ultraviolet light irradiation, mechanical damage or fungal infection [37][38][39][40][41]. A large number of in vitro and in vivo tests have shown that resveratrol can effectively prevent hypertension through antioxidant effects [42], cardiovascular diseases [43], nonalcoholic fatty liver [44], metabolic syndrome [45], aging [46], cancer [47], and immunological diseases [48], through its antioxidant effect, and has a good application prospect. Based on this, the research on the safety of resveratrol is meaningful.…”
Section: Discussionmentioning
confidence: 99%